Taxonomy of the Threadsnakes of the tribe Epictini (Squamata: Serpentes: Leptotyphlopidae) in Colombia - Pinto, Roberta Richard; Passos, Paulo; Portilla, José Rances Caicedo; Arredondo, Juan Camilo; Fernandes, Ronaldo (Zootaxa, 2010)
Threadsnakes of the tribe Epictini are endemic to the New World, occurring from the United States to Argentina, mostly in the Neotropical region. Currently, the taxonomic status of most species is unclear and there has been no previous attempt of a comprehensive taxonomic revision of Neotropical taxa. Taxonomy of the group is a difficult task due to the paucity of geographic samples, general homogeneous morphology and brevity of species descriptions. Therefore, the only way to address the taxonomic status of existing names is through detailed characterization of the types and the search for additional material of the poorly known species. In this study, we evaluated the taxonomic status of the Colombian threadsnakes and report on geographical variation of meristic, morphometric, colour pattern, and hemipenis characters. On the basis of available samples we recognize the following species in Colombia: Epictia goudotii, E. magnamaculata, E. signata, Rena nicefori, Tricheilostoma brevissimum, T. dugandi, T. joshuai and T. macrolepis. We discuss the systematic position of Rena nicefori and propose its allocation in the genus Tricheilostoma based on a unique combination of morphological characters. Furthermore, we provide a key to the representatives of the tribe Epictini in Colombia.